Behavioural risk-factors of hypertension and its knowledge in rural South India: a cross-sectional study - Alalageri, Kavya M.; B. R., Mahesh Murthy; Kumar, Revathi Arun (International Journal Of Community Medicine And Public Health, 2024)
Background: India, a lower middle-income country with a population of more than 1 billion is undergoing a rapid epidemiological transition characterized by an increased prevalence of non-communicable diseases. It is estimated to account for 10.8% of all deaths and 4.6% of all disability-adjusted life years in India. Hence this study is carried out to assess the socio-demographic profile and risk factors associated with hypertension (HTN) in rural India. and to determine the association between risk factors and hypertensive status. Methods: This is a community-based cross-sectional study in Shivamogga taluk of Karnataka from May-September 2023. Based on 2011 census, Shivamogga taluk has 117601 households bearing population of 507324 and sex-ratio 987 per 1000 males, 36.4% of population lives in urban area and 63.6% in rural area. Ayanur and Matthur are rural field practice area of SIMS having population of 3605 and 3144 respectively. The multi-stage random sampling method is used to study 430 study participants. Results: The study comprised of 430 participants, 162 (37.67%) were among the age group of 50-65 years, 223 (51.86%) were hypertensives and 306 (71.16%) stated that HTN adversely effects health of an individual. 381 (88.6%) opined that reducing salt intake in the diet can significantly reduce the development of HTN in an individual. Conclusions: HTN is a behavioural disease that is increasing day by day and there is no much difference between people living in urban/rural areas. Hence, this needs to be addressed at a primitive level to decrease the prevalence of NCD’s by promoting health, adopting healthy lifestyles and adherence towards medications.